Periprosthetic acetabular fractures: A New classification proposal. (November 2018) - Pascarella, R.; Sangiovanni, P.; Cerbasi, S.; Fantasia, R.; Consonni, O.; Zottola, V.; Panella, A.; Moretti, B.
Graphical abstract: Abstract: Introduction: Acetabulum periprosthetic fractures are rare, but are increasing, due to increase in high-energy trauma and a decrease in mortality index. Reconstruction of an acetabular fracture, in the presence of hip arthroplasty can be very complex and represents a real challenge for orthopedic surgeon. Aim of this multicentric study is to classify periprosthetic acetabulum fractures and to propose a treatment algorithm. Materials and methods: 24 cases of acetabular periprosthetic fracture were treated surgically from 01.01.2010 to 31.04.2017 in three different hospitals; 4 males and 20 females, average age 76 years (range 56–90 years). Treatment: 4 cases treated conservatively, 8 cases ORIF, 2 cases treated with acetabular ring and screws, 9 cases ORIF and acetabular cup revision, 1 implant removal without revision. Results: All cases were reviewed at minimum 12 months follow-up. In 22 cases, there was no need for new surgical procedures and radiographically all implants appeared stable and with good bone integration. In a case of a type 1b fracture, a dislocation of prosthetic implant was observed after 3 months. In a case prosthesis was explanted and it was not possible to perform a revision. Discussion and conclusions: Fracture classification systems must facilitate communication between surgeons and encourage documentation and research. However, they should also have prognostic value, so from them should come directly a treatment algorithm. In our experience, most important factors as prognostic and therapeutic predictors were: implant stability and timing of fracture: intraoperative or postoperative. In postoperative fractures CT is mandatory to evaluate cup mobilization and fracture patterns. Our classification proposal is simple and easy to remember for daily use. From it is derived a simple treatment plan.